Unraveling the Dynamics of e-Government Digitization, Penetration and User Experience: A Case Study of Greek Municipalities - Tsatsani, Olga; Patergiannaki, Zoi; Pollalis, Yannis (Journal of Strategic Innovation and Sustainability, 2024)
This study examines the user experience (UX) of Greek municipal websites, the first in-depth look at local e-Government services in Greece. Using Lighthouse for technical performance and an Adapted UX Audit, it explores factors beyond digital skills affecting citizen adoption of these platforms. Findings reveal widespread deficiencies, with no municipality scoring above 55%, highlighting significant challenges in usability, functionality, and user satisfaction. Critical issues in Technical Performance and Missing Features, both scoring below 50%, suggest that inherent design flaws hinder user acceptance. The study emphasizes the need for improvements in feedback mechanisms, multilingual support, and accessible help sections to better serve diverse populations. Addressing these gaps could enhance e-democracy by fostering more inclusive, user-friendly services. The results advocate for a strategic overhaul of municipal websites to increase engagement, improve e-Government effectiveness, and strengthen democratic participation. Limitations and recommendations for future research and policy-making are also provided.